EXPERIENCES IN APPLYING LESSONS LEARNED FROM THE LIVES OF MATURE INDIVIDUALS OF THE TIMURID PERIOD IN DIGITAL EDUCATION: https://doi.org/10.5281/zenodo.16812259 - Yusupova , Sadoqat (Journal of Contemporary World Studies, 2025)
The article analyzes the experiences of communicating lessons learned from the lives and activities of great figures who lived during the Timurid era to students through modern digital educational tools. The effectiveness of teaching historical resources using digital technologies (multimedia, virtual museums, interactive platforms) is shown on the basis of practical experience.